2021
DOI: 10.6000/1927-5129.2013.09.44
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Discomforts and Effect of Ingested Food in People Performing Hajj

Abstract: A variety of health issues have been investigated in the Hajj pilgrims (HPs) in KSA. However, it is still obscure to decide which meals contribute to health related issues specifically gastrointestinal disorders and allergies. Hence present study was planned to compare the effect of using different meals on GIT disorders and allergies. The data was categorized into two groups. Group 1 of age matched HPs comprised a Functional Digestive System Questionnaire (FDSQ) to study digestive disorders. Group 2 HPs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a systematic review of 15 studies of 262,999 pilgrims from 2002 to 2013 showed that the prevalence of diarrheal illness among pilgrimage was 2.3% (range: 1.1-23.3%) [21]. Cited risk factors for diarrhea among pilgrimage were: eating in restaurants [24] and being male [25,26], however, the source of food and eating raw vegetables were not associated significantly with the occurrence of 0 500,000 1,000,000 1,500,000 2,000,000 2,500,000 3,000,000 The Kingdom of Saudi Arabia, through its Ministry of Health, has provided curative and preventative medical services to all pilgrims through the establishment of several hospitals and clinics in the Hajj premises. One of its many mandates is to control any potential spread of infectious diseases during the Hajj [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of 15 studies of 262,999 pilgrims from 2002 to 2013 showed that the prevalence of diarrheal illness among pilgrimage was 2.3% (range: 1.1-23.3%) [21]. Cited risk factors for diarrhea among pilgrimage were: eating in restaurants [24] and being male [25,26], however, the source of food and eating raw vegetables were not associated significantly with the occurrence of 0 500,000 1,000,000 1,500,000 2,000,000 2,500,000 3,000,000 The Kingdom of Saudi Arabia, through its Ministry of Health, has provided curative and preventative medical services to all pilgrims through the establishment of several hospitals and clinics in the Hajj premises. One of its many mandates is to control any potential spread of infectious diseases during the Hajj [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review of 15 studies of 262,999 pilgrims from 2002 to 2013 showed that the prevalence of diarrheal illness among pilgrimage was 2.3% (range: 1.1-23.3%) [21]. Cited risk factors for diarrhea among pilgrimage were: eating in restaurants [24] and being male [25,26], however, the source of food and eating raw vegetables were not associated significantly with the occurrence of diarrhea [25]. Diarrheal illness was reported among 12% of attendees in the annual Arbaeen mass gatherings in Iraq [27] and among 4.5% among attendees of the 2015 Grand Magal [28] in one study, and 14.5% had gastrointestinal symptoms in another study [29].…”
Section: Introductionmentioning
confidence: 99%